Egerton Ryerson and the Mississauga, 1826 to 1856, an Appeal for Further Study - Smith, Donald (Ontario History, 2021)
The topic of Egerton Ryerson’s relationship with the First Nations is complex, a very large story. The key question returns again and again, what kind of relationship did the founder of Ontario’s school system have with the Indigenous Peoples? The focus of this article is on the First Nations group he knew best, the Mississauga, in particular the Credit Mississauga, the Ojibwe-speaking Anishinaabeg at the western end of Lake Ontario. As Ryerson is such a central figure in Ontario history, and even has a major university in the province named after him, I hope that young scholars, both Indigenous and non-Indigenous, will advance this discussion in future work.